2015
DOI: 10.3389/fonc.2015.00010
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Receptor Positive Lacrimal Sac Adenocarcinoma Demonstrating Long-Lasting Response to LHRH Analog Plus Abiraterone Treatment

Abstract: Tumors arising at the lacrimal sac are extremely rare, as a limited number of cases have been reported worldwide. They are commonly primary and the majority of them are malignant and epithelial in origin. Adenocarcinomas account for a small percentage of these tumors. Treatment of local disease mainly includes complete surgical resection. However, metastatic disease has a poor prognosis and the development of new treatment strategies is highly important. Research efforts mainly focus on the identification of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
(23 reference statements)
0
13
0
Order By: Relevance
“… 26 One previously described patient with AR-positive lacrimal sac adenocarcinoma showed an impressive response to antiandrogen treatment (abiraterone). 16 Our present patient was treated with a wide surgical resection followed by radiation therapy, and has survived for 16 months after surgery with no evidence of local recurrence or distant metastasis.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“… 26 One previously described patient with AR-positive lacrimal sac adenocarcinoma showed an impressive response to antiandrogen treatment (abiraterone). 16 Our present patient was treated with a wide surgical resection followed by radiation therapy, and has survived for 16 months after surgery with no evidence of local recurrence or distant metastasis.…”
Section: Discussionmentioning
confidence: 79%
“…Since Katz et al. reported the first case of ductal adenocarcinoma of the lacrimal gland in 1996 4 , only 16 further cases involvingthe lacrimal gland 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 and two involving the lacrimal sac 16 , 17 have been described ( Table 1 ). IHC for AR was performed in seven lacrimal gland and two lacrimal sac tumors, all of which showed positive results (100%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the potential to impede bacterial clearance, it has also been reported that PR3 itself possesses bactericidal properties through cleavage of the pro-microbicidal protein hCAP-18 (human cathelicidin) into the antibacterial peptide, mucus inducer and neutrophil chemo-attractant LL-37 [ 51 , 75 78 ]. Furthermore, levels of LL-37 in sputum are related to disease severity in patients with COPD suggesting an indirect role for PR3 which is worthy of further investigation [ 79 ].…”
Section: Pathophysiological Functions Of Proteinase 3 In Copdmentioning
confidence: 99%